Nigerian parents and caregivers knowledge, attitude and willingness to vaccinate their children against COVID-19 - Ajose, Azeezat; Akinde, Cassandra; Ilo, Azizat; Durojaiye, Tobi; Shittu, Yusuf; Kadiri, Tolani; Raheem, Bisola; Alamutu, Mujidat Kehinde; Ojo, Olamide; Roberts, Alero Ann (Frontiers in Public Health, 2023)
Objectives In order to achieve herd immunity against COVID-19, a significant proportion of the population will need to be vaccinated. Experts have recommended that African children be allowed to get vaccinated to protect them from emerging variants of COVID-19 infection. This study investigated Nigerian parents and caregivers’ knowledge, attitude, and willingness to vaccinate their children against COVID-19 once the vaccines are made available to them. Methods A cross-sectional online survey of 500 parents/caregivers was conducted in Nigeria. Participants were asked to complete a questionnaire about their sociodemographic characteristics, knowledge of and attitude toward COVID-19 infection and vaccination, willingness to vaccinate their child and factors that could influence their decision to vaccinate their child. A scoring system was used to classify the level of knowledge and attitude of participants into 2 categories, namely poor, and good. We analyzed data obtained using SPSS Version 22. Results Majority of the participants were females (63.6%). Analysis of responses revealed good knowledge and attitude in 265 (53.0%) and 266 (53.2%) respondents, respectively. Overall, less than half of the parents/caregivers (48.4%) expressed intention to vaccinate their children against COVID-19. Factors associated with willingness to vaccinate children against COVID-19 included age greater than 40 years, male gender, residing in Southern Nigeria, having good knowledge, knowing an infected person or a vaccinated person, feeling they or their child is at risk of contracting COVID-19 infection, willingness to vaccinate self against COVID-19 and good attitude. Significant predictors of willingness to vaccinate their child include age greater than 40 years [AOR: 2.56; 95% CI = (1.14–5.76)], willingness to vaccinate self [AOR: 1016.81; 95% CI = (128.51–8045.60)] and good attitude [AOR: 6.21; 95% CI = (2.83–13.64)]. Conclusion This study revealed that parental willingness to vaccinate their children against COVID-19 is low and identified factors influencing it. It is important to develop and implement health education programs iterating the risk of children getting infected with SARS-CoV-2 and its emerging variants to ensure optimal uptake of the COVID-19 vaccine in Nigerian children.